SOUTH TIBET (TAWANG) IN SINO-INDIAN RELATIONS - Rui Zhong (RUDN Journal of World History, 2015)
The article is devoted to the study of the special situation concerning Tawang region (is a part of the Indian state of Arunachal Pradesh, otherwise - Southern Tibet) in the Sino-Indian relations. In addition to its strategic positioning, and also because of demand of the PRC leadership to return China this region of the Tibet (TAR), Tawang gets the important place in the system of Tibetan Buddhism: it is the birthplace of the sixth Dalai Lama, and the current, Fourteenth leader of Tibetan Buddhism, who fled in 1959 from Lhasa into India via this area. According to the author, such combination of politics and religion is fraught with dangerous potential for conflict, which, in spite of the ongoing development of Sino-Indian relations and generally stable situation on the border, can in the shortest time create a real threat to the peaceful development of the border areas, and impact on the search of the new incarnation of the Dalai Lama.